2020
DOI: 10.3390/hydrology7020022
|View full text |Cite
|
Sign up to set email alerts
|

Disentangling the Main Components of Hydromorphological Modifications at Reach Scale in Rivers of Greece

Abstract: The Water Framework Directive (WFD) requires from member states to monitor hydromorphological features of rivers in order to assess their ecological quality. Thus, numerous hydromorphological assessment methods have been developed with most of them focusing on the dynamics of hydrology, geomorphology and riparian zone extent. Within the scope of this study, we assessed the hydromorphological features of 106 river reaches distributed among thirteen WFD River Basin Districts (RBDs) to identify the main drivers o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
0
12
0
Order By: Relevance
“…The construction of dams and barriers are among the most important factors for the decrease of the riparian vegetation, due to the hydrological regime's alterations. Recently, a study by Stefanidis et al [5] showed that bank and channel modifications (i.e., resectioning, reinforcement) were a common hydromorphologic modification in Greek rivers. These modifications are used as a flood defense management practice.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The construction of dams and barriers are among the most important factors for the decrease of the riparian vegetation, due to the hydrological regime's alterations. Recently, a study by Stefanidis et al [5] showed that bank and channel modifications (i.e., resectioning, reinforcement) were a common hydromorphologic modification in Greek rivers. These modifications are used as a flood defense management practice.…”
Section: Resultsmentioning
confidence: 99%
“…As a result, dams, bridges, weirs, channelization, embankments, deepening, resectioning, and many others are some examples of the modifications that threaten the river connectivity, the riparian corridor's naturalness, and the overall ecosystem health. Identifying these pressures at reach scale is often accomplished through monitoring activities in accordance with the implementation of the WFD [5].…”
Section: Riparian Vegetation and Hydromorphological Alterationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Agricultural activity in particular is considered a major driver of hydromorphological modifications in Mediterranean rivers [15][16][17]. For instance, bank and channel resectioning is used as a practice of flood defense management to protect neighboring agricultural land from flood events.…”
Section: Discussionmentioning
confidence: 99%
“…In addtion, bank reinforcement that uses hard materials (concrete, bricks, rip-rap, etc.) aims to mitigate bank erossion [17]. These changes inevitably are associated with significant alterations in the riparian zone affecting the structure and cover of the vegetation.…”
Section: Discussionmentioning
confidence: 99%